Behavior of Concrete Columns Repaired with Polymer Mortar and Epoxy Fiber Panel - Sungnam Hong; Sun-Kyu Park (Advances in Materials Science and Engineering)
Underwater structures are not easy to check for the degree of damage or to repair and strengthen damaged regions. Even during repair and strengthening, quality control is very difficult, because the work is done under water. Moreover, underwater structures severely deteriorate, owing to special environmental conditions. If this deterioration continues, the structures face serious structural problems, because of the corrosion of steel rods and the loss of concrete sections. Repairing or strengthening underwater structures requires effective, economic underwater repair and reinforcement techniques that allow the same working conditions as on the ground while maintaining dry condition for the repair sections. However, systematic studies on the repair and strengthening techniques for underwater structures are insufficient. This study proposes a new repair method for underwater structures, which applies epoxy fiber panel forms and shear connectors. To demonstrate the repair effects, this study compared and evaluated the failure modes and repair effects by the surface condition of repair sections, by applying various repair methods, in consideration of the ground and underwater conditions.